Anti-drug Antibody Sample Testing and Reporting Harmonization - Darshana Jani; Robin Marsden; Michele Gunsior; Laura Schild Hay; Bethany Ward; Kyra J. Cowan; Mitra Azadeh; Breann Barker; Liching Cao; Kristin R. Closson; Kelly Coble; Sanjay L. Dholakiya; et al. (The AAPS Journal, 2022)
A clear scientific and operational need exists for harmonized bioanalytical immunogenicity study reporting to facilitate communication of immunogenicity findings and expedient review by industry and health authorities. To address these key bioanalytical reporting gaps and provide a report structure for documenting immunogenicity results, this cross-industry group was formed to establish harmonized recommendations and a develop a submission template to facilitate agency filings. Provided here are recommendations for reporting clinical anti-drug antibody (ADA) assay results using ligand-binding assay technologies. This publication describes the essential bioanalytical report (BAR) elements such as the method, critical reagents and equipment, study samples, results, and data analysis, and provides a template for a suggested structure for the ADA BAR. This publication focuses on the content and presentation of the bioanalytical ADA sample analysis report. The interpretation of immunogenicity data, including the evaluation of the impact of ADA on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract